Education, Parity, and Health Worker Support Associations to Postpartum Care in Indonesian Context - Umaroh Umaroh; Martha Irene Kartasurya; Cahya Tri Purnami; Syamsulhuda Budi Mustofa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Maternal mortality during the postpartum period remains a significant public health concern. In 2022, most cases of maternal deaths in Semarang City occurred during postpartum period. Maternal knowledge and attitudes regarding postpartum selfcare are essential for preventing complications. Midwives’ visit to postpartum mothers’ program in Indonesia can be improved to increase mothers’ knowledge and attitude on postpartum care. This study aimed to investigate the factors associated to postpartum care in urban area of Indonesia. Methods: A cross-sectional study was conducted involving 90 postpartum mothers selected from three primary health care centers in Semarang City, which were chosen based on high numbers of postpartum mothers and demographic variations. Data were collected using validated, structured interviews to assess maternal knowledge, attitudes, and health worker support. Data were analyzed using Pearson correlation tests and multiple linear regressions to determine the associations between socio demographic factors and postpartum care indicators. Results: The average maternal knowledge score (8.2 ± 1.16), and the attitude score were good (22.2 ± 2.82). The knowledge of mothers was lack in face’s sign of preeclampsia. The attitude of mothers was lack in self-assessment on breast inflammation. Educational attainment (p = 0.061) and parity (p = 0.015) positively correlated to knowledge. Age (p = 0.014), parity (p = 0.049), and support from health workers (p = 0.041) significantly associated to maternal attitudes. Conclusion: Higher levels of education and strong support from health workers were associated to improved maternal knowledge and attitudes toward postpartum care. These findings showed the importance of interventions on postpartum care. Focusing on less educated mothers and enhancing healthcare engagement are important to reduce postpartum related complications and maternal mortality.